EPID-02. MALIGNANT PRIMARY BRAIN AND OTHER CENTRAL NERVOUS SYSTEM TUMOURS DIAGNOSED AMONG THE CANADIAN PAEDIATRIC POPULATION FROM 2009 TO 2013. Issue 2 (22nd June 2018) - Walker, Emily; Amjad, Sana; Davis, Faith; Surveillance, The CBTR; Group, Reporting Working
Abstract: The Canadian Brain Tumour Registry (CBTR) project was established in 2016 with the aim of enhancing infrastructure for surveillance and clinical research to improve health outcomes for brain tumour patients in Canada. We present a national surveillance report on malignant primary brain and central nervous system (CNS) tumours diagnosed in the Canadian paediatric population from 2009–2013. Patients aged 0–19 years were identified through the Canadian Cancer Registry (CCR); an administrative dataset that includes cancer incidence data from all provinces/territories in Canada. Cancer diagnoses are coded using the ICD-O3 system. Tumour types were classified by site and histology using the Central Brain Tumour Registry of the United States classification; and the International Classification of Childhood Cancer (ICCC). Incidence rates (IR) and 95% confidence intervals (CI) were calculated per 100, 000 persons and standardized to the 2011 census population. Overall, 1, 130 malignant brain and CNS tumours were diagnosed in the Canadian paediatric population from 2009–2013 (IR: 2.90; 95%CI: 2.74, 3.08). Of these, 625 were diagnosed among males (IR: 3.14; 95%CI: 2.89, 3.39) and 505 among females (IR: 2.66; 95%CI: 2.43, 2.90). The most common ICCC classification was III(b)-Astrocytomas (IR: 1.05; 95%CI: 0.95, 1.16). The most common histology by age group was: 0–4 years: Embryonal tumours (IR: 1.07; 95%CI: 0.88, 1.30); 5–9 years: Pilocytic Astrocytoma (IR: 0.88; 95%CI: 0.71, 1.10); 10–14 years: Pilocytic Astrocytoma (IR: 0.62; 95%CI: 0.49, 0.80); and 15–19 years: Pilocytic Astrocytoma (IR: 0.41; 95%CI: 0.31, 0.55). The presentation will include: IRs for both classifications, histology groups, geographic distribution and a comparison between Canada and the United States.